2015
DOI: 10.1093/gbe/evv254
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive tRNA Genomic Survey Unravels the Evolutionary History of tRNA Arrays in Prokaryotes

Abstract: Considering the importance of tRNAs in the translation machinery, scant attention has been paid to tRNA array units defined as genomic regions containing at least 20 tRNA genes with a minimal tRNA gene density of two tRNA genes per kilobase. Our analysis of Acidithiobacillus ferrivorans CF27 and Acidithiobacillus ferrooxidans ATCC 23270T genomes showed that both display a tRNA array unit with syntenic conservation which mainly contributed to the tRNA gene redundancy in these two organisms. Our investigations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 46 publications
6
34
0
Order By: Relevance
“…An analysis of tRNA clusters in members of acidithiobacilli revealed that an array similar to that in ICEAfe1 is present in A. ferrivorans, another acidophilic bacterium belonging to the consortium of bioleaching microorganisms. Our phylogenetic data on the cluster of tRNA genes encoded in ICEAfe1 from A. ferrooxidans ATCC 23270 is consistent with the data presented by Tran et al 15 that includes the tRNA gene cluster from A. ferrivorans. Taken together, these data predict that these 2 arrays were acquired by HGT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An analysis of tRNA clusters in members of acidithiobacilli revealed that an array similar to that in ICEAfe1 is present in A. ferrivorans, another acidophilic bacterium belonging to the consortium of bioleaching microorganisms. Our phylogenetic data on the cluster of tRNA genes encoded in ICEAfe1 from A. ferrooxidans ATCC 23270 is consistent with the data presented by Tran et al 15 that includes the tRNA gene cluster from A. ferrivorans. Taken together, these data predict that these 2 arrays were acquired by HGT.…”
Section: Discussionsupporting
confidence: 92%
“…Although not all tRNA genes present in ICEAfe1 are encoded in this cluster, a similar synteny was found indicating probably a common origin. 15 A global analysis in the genus Acidithiobacilli revealed that codon usage of these 2 species is very similar (S6 Fig. 2), thus we believe that the effect on tAI of the cluster of tRNAs should also be similar in the 2 species.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Besides mitogenomes, tRNA gene clusters have been shown to be abundant in Eukarya (Tawari et al, 2008;Bermudez-Santana et al, 2010). In prokaryotes, tRNA gene clusters were characterized in some bacteria, being prevalent in Firmicutes phylum and Mycobacterium genus (Tran et al, 2016;Morgado and Vicente, 2018), while in archaea, the presence of one tRNA gene cluster was only identified in the Methanobrevibacter M1 strain genome (Tran et al, 2016). Considering the common features among the three domains of life we hypothesized the prevalence of tRNA gene cluster also in archaea.…”
Section: Introductionmentioning
confidence: 96%
“…in bacteria are ribosomal RNA (rRNA) and transfer RNA (tRNA) operons [8,9]. There are several reasons for the interest in these operons, since those genes are fundamental for protein synthesis, and their numbers and organization can be used to better understand codon usage [10].…”
mentioning
confidence: 99%